2021
DOI: 10.1038/s41598-021-92250-8
|View full text |Cite
|
Sign up to set email alerts
|

Impaired auditory discrimination and auditory-motor integration in hyperfunctional voice disorders

Abstract: Hyperfunctional voice disorders (HVDs) are the most common class of voice disorders, consisting of diagnoses such as vocal fold nodules and muscle tension dysphonia. These speech production disorders result in effort, fatigue, pain, and even complete loss of voice. The mechanisms underlying HVDs are largely unknown. Here, the auditory-motor control of voice fundamental frequency (fo) was examined in 62 speakers with and 62 speakers without HVDs. Due to the high prevalence of HVDs in singers, and the known impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 48 publications
4
21
0
Order By: Relevance
“…These results are suggestive of an impairment in auditory discrimination functional (MTVD) and neurological voice-disordered individuals. These data congruent with work by Abur et al [4] who showed that the auditory discrim threshold was significantly larger in patients with hyperfunctional voice disorder = 47 cents, SD = 32 cents) than in control participants (mean = 35 cents, SD = 20 cen differences in the auditory discrimination thresholds between our current data a study likely stemmed from the study design and type of test stimuli. Here, we did the just-noticeable-difference (JND) in pitch, but rather used pure tones.…”
Section: Pitch Discrimination In Voice-disordered Patientssupporting
confidence: 93%
See 4 more Smart Citations
“…These results are suggestive of an impairment in auditory discrimination functional (MTVD) and neurological voice-disordered individuals. These data congruent with work by Abur et al [4] who showed that the auditory discrim threshold was significantly larger in patients with hyperfunctional voice disorder = 47 cents, SD = 32 cents) than in control participants (mean = 35 cents, SD = 20 cen differences in the auditory discrimination thresholds between our current data a study likely stemmed from the study design and type of test stimuli. Here, we did the just-noticeable-difference (JND) in pitch, but rather used pure tones.…”
Section: Pitch Discrimination In Voice-disordered Patientssupporting
confidence: 93%
“…This suggests vo order types and/or dysphonic severity may not be linked to the auditory perceptio tion. This finding appeared to agree with observations by Abur et al [4] who fo relationship between the overall severity of dysphonia and auditory discrim…”
Section: Pitch Discrimination In Voice-disordered Patientssupporting
confidence: 92%
See 3 more Smart Citations